â€œPLACE ATTACHMENTâ€ PEMUKIM PASCARELOKASI DI KOTA PALU - Batudoka, Zubair (MEKTEK, 2005)
The limited of land and accesibility of the low income people in Palu city caused the growth of illegal informal settlements. Within its settlement development programs, the local government of Palu was applying a relocation policy. Relocation of the informal coast settlement for Besusu Barat and Talise district to Layana Indah in North Palu. After the relocation (pascarelokasi) some of dwellers behave the resisting, some of other hold out at settlement after the relocation. This condition showed the â€œplace attachmentâ€. Research to